When does a self-serving antitrust authority act in society's best interests? - Joseph Emmett Harrington (The Johns Hopkins University, Department of Economics, 2009)
If an antitrust authority chooses policies to maximize the number of successfully prosecuted cartels, when do those policies also serve to minimize the number of cartels that form? When the detection and prosecution of cartels is inherently difficult, we find that an antitrust authority's policies minimize the number of cartels, as is socially desirable. But when the detection and prosecution of cartels is not difficult, an antitrust authority is not aggressive enough in that it prosecutes too few cartel cases.
Keywords: 330; Konzentrationspolitik; Wohlfahrtseffekt; Theorie